2012
DOI: 10.2147/cia.s34789
|View full text |Cite
|
Sign up to set email alerts
|

Falls in nursing home residents receiving pharmacotherapy for anemia

Abstract: PurposeFalls are common among nursing home residents and have potentially severe consequences, including fracture and other trauma. Recent evidence suggests anemia may be independently related to these falls. This study explores the relationship between the use of anemia-related pharmacotherapies and falls among nursing home residents.MethodsForty nursing homes in the United States provided data for analysis. All incidents of falls over the 6-month post-index follow-up period were used to identify the outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Patients with anemia below 11 g/100 mL also have significantly decreased scores for activities of daily life and quality of life [130]. Second, even though at least one study has shown no associations between anemia and decreases for community-living elderly individuals [131], such an association has been observed for nursing home residents [132,133]. Third, frailty has been defined as a medical syndrome characterized by decreased physiological reserve and increased vulnerability, and frailty seems to be a predictor for nursing home placement of elderly community-dwelling individuals [134].…”
Section: Robinson Et Al [126]mentioning
confidence: 99%
“…Patients with anemia below 11 g/100 mL also have significantly decreased scores for activities of daily life and quality of life [130]. Second, even though at least one study has shown no associations between anemia and decreases for community-living elderly individuals [131], such an association has been observed for nursing home residents [132,133]. Third, frailty has been defined as a medical syndrome characterized by decreased physiological reserve and increased vulnerability, and frailty seems to be a predictor for nursing home placement of elderly community-dwelling individuals [134].…”
Section: Robinson Et Al [126]mentioning
confidence: 99%
“…(The present paper will not address the case of hemoglobinopathy, which is specific). Anemia in the aged increases frailty, impacts cardiovascular and coronary circulation, dampens cognitive potential, and favors falls and fractures; anemia increases mortality, hospitalization, difficulty of mobility, difficulty with daily life, and fatigue [10][11][12][13][14][15].…”
mentioning
confidence: 99%